Journalists and aid workers – an ambivalent relationship - Florian Westphal (Asia Pacific Network, 2010)
Commentary: The relationship between the news media and humanitarians remains extremely important as both play a key role in terms of shaping of what we know and how we experience armed conflicts of which most of us have no first-hand knowledge. By shaping public perceptions, these two actors also influence the actions taken by governments and the international community to put an end to or alleviate the suffering caused by wars. Yet, as this keynote address at the Reporting Wars conferences in Sydney and Wellington in May 2009 seeks to explain, there is nothing automatic about this process.